До проблеми генетичної ідентичності видового складу дендрологічних колекцій ботанічних садів - Gorb, V.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
In botanical gardens many species within the limits of one plant genus, growing side by side, are capable to interpollinate with a formation of viable seeds. This seeds, owing to Index seminum, enter other botanical gardens, filling their collections not with certain species but rather with their hybrids. Seed for an exchange between botanical gardens are proposed to collect: a) in nature; b) from plants of those species which do not interpollinate spontaneously; c) from plants which are spationally isolated from potenial pollinators. The author suggests to replant collections of botanical gardens step by step so that there was a spatial isolation between species, capable to pollination between themselves.